IMPLEMENTATION OF DIGITAL MARKETING TO IMPROVE MARKETING AT MIORI FARM WOMEN’S FARMERS GROUP - Manalu, Doni Sahat Tua; Andalusia, Hazzahra; Ramadani, Zahra Afrina; Housheki S., Azzahro; Maulana, Hanifa Zulfa; Firdaos; Kartika, Sartiva Dinda (Jurnal Hexagro, 2025)
The Miori Farm Women's Farmers Group, rooted in a rural agrarian setting, faces persistent challenges in accessing broader markets and enhancing the visibility of its agricultural products. Traditional marketing approaches have limited their reach, income potential, and ability to compete in dynamic value chains. In response, digital marketing emerges as a strategic solution to bridge these gaps. By leveraging digital platforms—such as Instagram, Shopee, and TikTok this initiative empowers women farmers with tools for brand development, direct consumer engagement, and real-time market intelligence. Digital marketing supports income diversification and product value addition and fosters inclusive growth, gender equity, and sustainable rural entrepreneurship. This research examines the application of digital marketing in improving the marketing performance of the Miori Farm Women's Group in Cianjur. Using a mixed-methods approach, the study analyzes consumer preferences through conjoint analysis and surveys to assess the role of digital marketing in expanding market reach. Findings indicate that Miori Farm has established a local market presence and holds potential for growth through effective online strategies. This study provides insights into how digital marketing can enhance the competitiveness and sustainability of agricultural products in the digital era.